An International Outburst of New Form of Monkeypox Virus - Kiran Dobhal; Pallavi Ghildiyal; A.N.M. Ansori; Vikash Jakhmola (Journal of Pure and Applied Microbiology, 2022)
A new strain of the old pandemic, Monkeypox (MPX), has emerged with a more complicated clinical appearance. It is a source of relief that the fatality rate in the new monkeypox is lower, but communicability is higher. This infection’s diagnosis and therapy are still challenging and unknown. Researchers are reporting increased human-to-human transmission in the modified version of MPX. There have been several reports of the updated version of monkeypox in the European and American areas. Brazil, Colombia, France, Spain, Germany, Peru, the United Kingdom, and the United States of America have recorded over three thousand new cases of monkeypox through October 2022. Few antiviral medicines and vaccines are available on the market, making treatment of this condition difficult. MPX was previously declared an epidemic disease, but ignorance about it can bring devastation in the shape of the next pandemic-like COVID-19. This review aims to assess the virology, transmission, diagnosis, and therapy of MPX.